An Economic, Modular, and Portable Skin Viscoelasticity Measurement Device for In Situ Longitudinal Studies - Park, Seungman; Tao, Jiaxiang; Sun, Li; Fan, Chen-Ming; Chen, Yun (Molecules (Basel, Switzerland), 2019)
A indentation-based device to measure tissue mechanical property was designed and built using over-the-counter and 3D-printed parts. The device costs less than 100 USD and is capable of measuring samples of various geometry because of its modular design. The device is light-weight, thus portable, for measurements that can be performed at different sites. It was demonstrated that the measurement results obtained using our device are comparable to previous observations. The elastic shear modulus of the human skin was in the range of 2 kPa to 8 kPa, and skin tissues in old mice were stiffer than young mice. Mechanical properties of the skin tissues belonging to the same test subject varied depending on the location of the measurement. In conclusion, because our device is economic, modular, portable, and robust, it is suitable to serve as a standard measurement platform for studying tissue mechanics.